2019
DOI: 10.1101/837344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the Clostridial cellulose synthase and characterization of the cognate glycosyl hydrolase, CcsZ

Abstract: 1Biofilms are community structures of bacteria enmeshed in a self-produced matrix of exopolysaccharides. 2The biofilm matrix serves numerous roles, including resilience and persistence, making biofilms a subject 3 of research interest among persistent clinical pathogens of global health importance. Our current 4 understanding of the underlying biochemical pathways responsible for biosynthesis of these 5 exopolysaccharides is largely limited to Gram-negative bacteria. Clostridia are a class of Gram-positive, 6 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…We also noted that at 48h of incubation, proteins form clusters in all conditions, although this should be interpreted cautiously as PFA is known to form such protein aggregates. Interestingly, we observed that EPS are uniformly localized on top of the cells for all conditions tested, which is consistent with the expression of the ccsA gene (CD630_25450) encoding C. difficile's cellulose synthase (56), not significantly differentially regulated (Table S2) (10). Such distribution of EPS is probably due to their production only by cells localized at the top of the biofilm, by a division of labor similar to what was observed in B. subtilis (57).…”
Section: Discussionsupporting
confidence: 83%
“…We also noted that at 48h of incubation, proteins form clusters in all conditions, although this should be interpreted cautiously as PFA is known to form such protein aggregates. Interestingly, we observed that EPS are uniformly localized on top of the cells for all conditions tested, which is consistent with the expression of the ccsA gene (CD630_25450) encoding C. difficile's cellulose synthase (56), not significantly differentially regulated (Table S2) (10). Such distribution of EPS is probably due to their production only by cells localized at the top of the biofilm, by a division of labor similar to what was observed in B. subtilis (57).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, selectively targeting biofilms using GH enzymes might be feasible. A list of these enzymes used for biofilm dispersion is shown in Table 2 ( 135 , 139 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ).…”
Section: Enzymatic Degradation Of Polysaccharides—an Emergent Approac...mentioning
confidence: 99%